como resolve?
![n + 2 = 4(n - 1) n + 2 = 4(n - 1)](https://tex.z-dn.net/?f=n+%2B+2+%3D+4%28n+-+1%29)
Soluções para a tarefa
Respondido por
1
Olá, boa noite ☺
Resolução:
n + 2 = 4(n -1)
n +2 = 4n - 4.
n - 4n = -4 - 2.
- 3n = - 6. (-1).
3n = 6.
n=6/3.
n=2.
Bons estudos :)
Resolução:
n + 2 = 4(n -1)
n +2 = 4n - 4.
n - 4n = -4 - 2.
- 3n = - 6. (-1).
3n = 6.
n=6/3.
n=2.
Bons estudos :)
Perguntas interessantes
Português,
11 meses atrás
Inglês,
11 meses atrás
Biologia,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás